Survey on Fault Operation on Multilevel Inverters - Lezana, Pablo; Pou, Josep; Meynard, Thierry A.; Rodriguez, Jose; Ceballos, Salvador; Richardeau, Frédéric (IEEE transactions on industrial electronics (1982), 2010)
This paper is related to faults that can appear in multilevel (ML) inverters, which have a high number of components. This is a subject of increasing importance in high-power inverters. First, methods to identify a fault are classified and briefly described for each topology. In addition, a number of strategies and hardware modifications that allow for operation in faulty conditions are also presented. As a result of the analyzed works, it can be concluded that ML inverters can significantly increase their availability and are able to operate even with some faulty components.